PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA TANAMAN PANGAN DAN HORTIKULTURA KABUPATEN PASER - Indah Febrianti Alman; Achmad Syahruddin; Mustaqiem (PIRSAP (Paser Institute for Scientific Research and Publications), 2023)
The purpose of this study was to determine the effect of leadership style on employee performance at the District Horticulture and Food Crops Service. Paser The location of the research was carried out at the Department of Food Crops and Horticulture, Paser Regency. The purpose of this study was to determine the effect of leadership style which includes the variables of Autocratic Leadership Style (X,), Democratic Leadership Style (X2), and Laissez-faire Leadership Style (X) on Employee Performance (Y) in the District Food Crops and Horticulture Service. Paser. This type of research is quantitative research with the analytical tool used is multiple linear regression analysis processed with the help of SPSS (Statistical Packages For Social Sciences). From the results of the study, the results of the validity test were obtained from the number of questions as many as 13 items, all of which had an r count value that was more than the rasset value = 0.2480, which meant that all questions were valid. From the results of the reliability test, it can be seen that a result of 0.785 is obtained, which means that the questionnaire items can be said to be reliable (proper) because Cronbach's Alpha > 0.6. The regression equation Y=-0.077 + 0.300 X + 0.718 X + 0.012 X. The magnitude of the correlation coefficient (R) is 0.767. This shows that there is a strong relationship between the variables of Autocratic Leadership Style (X,), Democratic Leadership Style (X), Laissez-Faire Leadership Style (X) on Employee Performance (Y) in the Food Crops and Horticulture Office of Paser Regency. While the coefficient of determination (R2) is 0.588. This shows that 58.8% variation or change in the value of the dependent variable (employee performance) can be explained by the independent variable (leadership style) consisting of autocratic leadership style (X), democratic leadership style (X2), laissez-faire leadership style (X) , then 41.2% is influenced by other variables not examined.